Self Modeling Mengatasi Kecemasan Mahasiswa dalam Menghadapi Dosen Pembimbing - Syafri, Fatrida Anugrah; Sasongko, Rambat Nur; Kristiawan, Muhammad; Yuliarsih, Flen (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to see the effectiveness of the services provided on the level of anxiety of final year students towards their supervisors. This study uses experimental research methods. In this study, counseling services were carried out using self-modeling techniques to relieve final year students' anxiety towards their supervisors, this research was an experimental study with an experimental design, where the sample in this study was single subject research. Based on the results of the study, the type of counseling service with self-modeling techniques was proven to reduce the level of anxiety of final semester students towards their supervisors, marked by a significant change from the baseline state to a better level after the intervention with a decrease in score of 10.58. In conclusion, individual counseling with self-modeling techniques is generally effective in developing self-confidence and reducing the level of anxiety of final year students in dealing with supervisors. Keywords: Self Confidence, Anxiety, Self Modeling